Digital language teacher professional development in online community of practice: Indonesia-Vietnam perspective - La Ode Nggawu; Jamiludin Jamiludin; Darnawati Darnawati; Waode Ade Sarasmita Uke; Ismail Anas; Nguyen Thi Phuong Thao; Võ Thị Anh Thư (Intelektual Pustaka Media Utama, 2026)
This study investigates digital language teacher professional development (TPD) within online communities in Indonesia and Vietnam, employing Pinar’s currere framework to identify optimal practices. Through qualitative methods, including interviews and observations, this study examined the experiences of English language educators navigating digital education in these countries. The findings indicate that, while both nations emphasize the significance of digital literacy, educators encounter challenges in acquiring essential digital competencies due to limited resources and infrastructure. Online communities of practice (CoPs) function as valuable platforms for knowledge dissemination, peer support, and professional growth, enabling teachers to enhance their digital proficiency. However, issues such as internet accessibility, time constraints, and language barriers persist as obstacles. This investigation underscores the necessity for tailored TPD programs that address these specific challenges, ultimately fostering effective integration of technology into language instruction.